On the Integration of Carbon Capture and Storage into the International Climate Regime - Sven Bode; Martina Jung (Hamburg Institute of International Economics (HWWA), 2004)
As GHG emissions did not decline as anticipated early of the 1990ties Carbon Capture and Storage (CCS) recently gained more and more attention as a climate change mitigation option. However, CO2 suppressed in geological reservoirs is likely to lead to future releases of the CO2 stored. This ,,non-permanence“ must be considered if an environmentally sound policy is desired. Against this background, the present article analyses a potential integration of CCS in the international climate regime. It is based on existing rules and modalities regarding non-permanence of sequestration in the Land use, Land-use change and Forestry (LULUCF) sector. Interestingly, the experience from LULUCF has almost completely been neglected during the discussion on CCS. We argue that CCS can only be accounted for in a transparent and comprehensive way, if it is considered a ,,removal“ (or ,,sink“) activity. This is, however, incompatible with the current UNFCCC rules and definitions. Consequently, they would have to be changed. Accounting and problems of cross-border projects are discussed. They arise due to the potential geographical separation of capture and storage site. Furthermore, an economic analysis is conducted considering the consequences of non-permanent storage. We apply the tCER approach for LULUCF projects which has already been agreed upon during the international climate negotiations. It may thus form the basis for CCS, too. The study suggests that CCS is probably not as attractive as widely claimed.
Keywords: Q38; Q48; Q28; Q25; 330; Carbon Dioxide Capture and Storage; Permanence; Sequestration; LULUCF; Climate Policy; Klimaschutz; Kohlendioxid; Forstwirtschaft; Umweltabkommen; Welt; Kohlendioxidsenke; Carbon dioxide sinks